THE ROLE OF OPERATIONAL AUDIT IN IMPROVING THE EFFECTIVENESS OF THE INTERNAL CONTROL SYSTEM IN PT. BANK RAKYAT INDONESIA (PERSERO) Tbk. ENDE - Sabra B. Wahab Thalib; Nuraini Ismail (Jurnal Ekonomi, 2022)
In conducting business and banking operations, risk problems cannot be avoided or completely eliminated, but at least these risks can be identified and suppressed in order to reduce them. Internal audit activity is to examine and assess the effectiveness and adequacy of the existing internal control system within the organization. Without an internal audit function, the board of directors or unit leadership cannot have an independent source of internal information regarding organizational performance. Internal audit basically aims to provide assistance to management and the board of directors in carrying out their responsibilities effectively, including efforts to develop effective controls at a reasonable cost. An effective internal control system is an important component in bank management and forms the basis for sound and safe bank operations. This study aims to determine the effectiveness of bank internal control in bank operational activities, especially in the administration of deposits, loans and cash. Qualitatively, data were collected which were then concluded without formulating a hypothesis. The data was obtained by using the library method and the field method with observation, documentation and interview techniques. The results of research on bank internal control found that internal control was still less effective, especially in terms of cash administration, deposits and loans.